(untitled) (Experimental biology, 2015)
Ecological safety is the process of environment prevention from anthropogenic or natural factors. Ecological environment control is the important hygienic task; by this reason the conception of the global ecological safety and ecological culture is a principal things for resisting against threats to life, health and prosperity.